PENGARUH CUSTOMER EXPERIENCE TERHADAP KEPUASAN KONSUMEN PRODUK KULINER LOKAL SOTO MBOK GEGER PEDAN KLATEN - Indah Handaruwati (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2021)
This study aims to obtain empirical evidence of the effect of Sensory Experience, Emotional Experience, Social Experience on Customer Satisfaction at Warung Soto Mbok Geger Pedan Klaten. The hypotheses proposed in this study are H1: It is suspected that Sensory Experience has a positive and significant influence on Customer Satisfaction, H2: It is suspected that Emotional Experience has a positive and significant effect on Customer satisfaction, H3: It is suspected that Social Experience has a positive and significant effect on Consumer Satisfaction at Warung Soto Mbok Geger Pedan Klaten, H4: It is suspected that the variable Sensory Experience, Emotional Experience, Social Experience simultaneously have a positive and significant effect on consumer satisfaction at Warung Soto Mbok Geger Pedan Klaten. The population in this study were 100 consumers of Warung Soto Mbok Geger Pedan Klaten. Sampling used the purposive sampling method, namely respondents with the criteria of having bought Soto Mbok Geger Pedan at least 1 time and the respondent had eaten at Warung Soto Mbok Geger Pedan, and the Convience Sampling method, namely respondents who were easy to find and had time to fill out the questionnaire. The results showed that Sensory Experience had a significant effect on Customer Satisfaction with a value of t count> t table, namely t count of 6,512 and t table of 1.98 with a significance of 0,000. Emotional Experience does not have a significant effect on customer satisfaction seen from the results of the t value <t table, which is equal to t count 0.302 and t table 1.98 with a significance of 0.763. Social Experience has a significant effect on customer satisfaction with a value of t count> t table, namely t count of 4.599 and t table of 1.98 with a significance of 0.000. The Customer Experience variable consisting of Sensory Experience, Emotional Experience, Social Experience has a simultaneous and significant effect, namely f count> f table, namely f count of 47.559 and f table of 2,700 with a significance value of 0,000. The Sensory Experience variable has the most dominant influence on Customer Satisfaction, which is 6,512.